Knowledge Map of Human Capital Development: A Scientometric Study Using VOSviewer - Judijanto, Loso; Prasetya, Yanto Budi (West Science Journal Economic and Entrepreneurship, 2025)
This study presents a comprehensive scientometric analysis of global research on human capital development (HCD) using VOSviewer to map its intellectual structure, thematic evolution, and collaborative networks. Bibliographic data were retrieved from the Scopus database, covering the period 2000–2025, and analyzed through co-authorship, co-citation, keyword co-occurrence, overlay, and density mapping techniques. The results reveal that human capital development remains the central research theme, strongly linked to economic growth, economic development, and increasingly to sustainable development, reflecting a shift towards integrating economic and sustainability paradigms. The co-authorship network highlights the United States as the primary research hub, with emerging contributions from Nigeria, Malaysia, and the Russian Federation, indicating both concentration and diversification of scholarly influence. Keyword overlay analysis shows recent research trends moving toward sustainability, globalization, and inclusive labor market outcomes, while density mapping confirms economic and sustainability themes as the conceptual core of the field. These findings provide actionable insights for policymakers, academics, and practitioners seeking to design integrated strategies that balance economic performance, environmental stewardship, and social equity in human capital policies. The study contributes to theory by reinforcing the need for multidisciplinary frameworks and offers a practical reference for guiding future HCD research agendas.